If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -7)(4x + 5) = 10x(2x + -1) Reorder the terms: (-7 + 5x)(4x + 5) = 10x(2x + -1) Reorder the terms: (-7 + 5x)(5 + 4x) = 10x(2x + -1) Multiply (-7 + 5x) * (5 + 4x) (-7(5 + 4x) + 5x * (5 + 4x)) = 10x(2x + -1) ((5 * -7 + 4x * -7) + 5x * (5 + 4x)) = 10x(2x + -1) ((-35 + -28x) + 5x * (5 + 4x)) = 10x(2x + -1) (-35 + -28x + (5 * 5x + 4x * 5x)) = 10x(2x + -1) (-35 + -28x + (25x + 20x2)) = 10x(2x + -1) Combine like terms: -28x + 25x = -3x (-35 + -3x + 20x2) = 10x(2x + -1) Reorder the terms: -35 + -3x + 20x2 = 10x(-1 + 2x) -35 + -3x + 20x2 = (-1 * 10x + 2x * 10x) -35 + -3x + 20x2 = (-10x + 20x2) Add '-20x2' to each side of the equation. -35 + -3x + 20x2 + -20x2 = -10x + 20x2 + -20x2 Combine like terms: 20x2 + -20x2 = 0 -35 + -3x + 0 = -10x + 20x2 + -20x2 -35 + -3x = -10x + 20x2 + -20x2 Combine like terms: 20x2 + -20x2 = 0 -35 + -3x = -10x + 0 -35 + -3x = -10x Solving -35 + -3x = -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -35 + -3x + 10x = -10x + 10x Combine like terms: -3x + 10x = 7x -35 + 7x = -10x + 10x Combine like terms: -10x + 10x = 0 -35 + 7x = 0 Add '35' to each side of the equation. -35 + 35 + 7x = 0 + 35 Combine like terms: -35 + 35 = 0 0 + 7x = 0 + 35 7x = 0 + 35 Combine like terms: 0 + 35 = 35 7x = 35 Divide each side by '7'. x = 5 Simplifying x = 5
| 5n+3+4n=24 | | 8(v-5)+(5-3v)=1-2v-6-v | | 1+4x-7x=-5 | | 5(m+7)+8=-5m-34 | | -7x+1-6x=-90 | | -b=-30 | | 7x+4-x=28 | | 2n^2+8n-64=0 | | 3+7x-2x=8 | | 3+2x+7x=-105 | | 4x+4-6x=-14 | | 10s-19=51 | | 32=2x+2x+8 | | -3+3x+3x=51 | | -2a+1=2(-3a-4)-3 | | 5x+8+3x+(-x)+5=6x+(-3) | | -2x+3=3+4 | | -15=3x-2x-5 | | 19p+17q+p-5q-4p= | | -14+v=0 | | K(y)=3y^2-9 | | 6x+7=5x-2 | | 3=m-5 | | 7(8+5p)=23+2p | | K(y)=0 | | -8=6+r | | 8*x+13=18 | | 3(20b)=36 | | 3w+5=2(w-1) | | 7(2n+6)=168 | | k-(-3)=12 | | 4x+15-2x+15=2 |